2020
DOI: 10.1007/s11845-020-02283-7
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic negative pressure wound therapy for closed laparotomy wounds: a systematic review and meta-analysis of randomised controlled trials

Abstract: Surgical site infections are a common source of post-operative morbidity and contribute significantly to healthcare costs. Patients undergoing emergency laparotomy and/or bowel surgery are particularly at risk. Prophylactic negative pressure wound therapy (NPWT) has been shown to reduce wound infection. However, to date, there has been a lack of consensus around its use for closed laparotomy wounds. We conducted a systematic review of randomised controlled trials comparing the use of prophylactic negative pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 46 publications
(39 reference statements)
1
33
0
2
Order By: Relevance
“…Thus, results of systematic reviews are often incorporated into clinical practice guidelines [35]. Regarding the prevention of SSIs by NPWT, three meta-analysis have been reported so far [2,10,11]. In 2018, Sahebally et al [10] reported a meta-analysis on NPWT for SSI prophylaxis, pooling six observational studies and three RCTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, results of systematic reviews are often incorporated into clinical practice guidelines [35]. Regarding the prevention of SSIs by NPWT, three meta-analysis have been reported so far [2,10,11]. In 2018, Sahebally et al [10] reported a meta-analysis on NPWT for SSI prophylaxis, pooling six observational studies and three RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current literature is not conclusive and has controversial results [1,2,4,[7][8][9]. General abdominal surgery has higher rates of SSIs compared with orthopedic, cardiothoracic, and other types of interventions [3,6] and previous meta-analyses on abdominal surgery have also reported contradicting results [2,10,11]. As a result of new trial results, we conducted this updated systematic review and meta-analysis to re-evaluate the value of prophylactic NPWT in general abdominal surgery after primary wound closure.…”
mentioning
confidence: 99%
“…Cannula site infection is a still fatal complication causing sepsis, especially in patients with extracorporeal BiVADs. In addition to antibiotics and surgical debridement, a VAC system has been used for treatment of VAD driveline and cannula site infections, 2,5–7 as well as for other types of surgical wounds, 8 to promote granulation tissue formation. Although VAC therapy of infection for those with extracorporeal VADs has already been reported, the outcome of prophylactic VAC management of BiVAD for such a long duration as in the present report is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…A wound bundle, in general, will have more than three components and extend from pre-operative care through to rehabilitation. Newer concepts in colorectal surgery wound care include negative pressure therapy [8] and wound protective devices [9,10].…”
Section: Introductionmentioning
confidence: 99%